IMPLEMENTASI THE POWER OF TWO UNTUK MENINGKATKAN KEMAMPUAN MENGAJAR MAHASISWA DALAM MICROTEACHING - Muh. Waskito Ardhi (Jurnal Pendidikan, 2013)
This study implements the power of two strategy on subject microteaching. The purpose of this study was to determine effect and improvement students teaching competence use of the power of two strategy. The method of this study was qualitative descriptive. Subject of study were student microteaching lecture class VIB of VIB1 group in biology department Faculty of Mathematic and Natural Science Education IKIP PGRI MADIUN Academic Year 2013/2014. The data obtained through assessment sheets using two instruments. That are learning plan and learning practice instruments. The results of this study showed an increase in the value of the average student in the learning plan. The average on first meeting was 2.80, second meeting 3.02 before apply the power of two strategy, became 3.50 in third meeting and 3.81 in fourth meeting after apply increase the power of two strategy. The average increase also occurred in leaning practice. The average on first practice learning was 3.01, second practice learning was 3.06 before apply the power of two strategy, became 3.30 in third practice learning and 3.52 in fourth practice learning after apply the power of two strategy.